2017
DOI: 10.1590/0103-8478cr20160590
|View full text |Cite
|
Sign up to set email alerts
|

Development of a weight-estimation model to use in pregnant criollo-type mares

Abstract: The aims of this study were: 1) to compare the tape weight and associated weight-estimation formula to evaluate weight gain in pregnant mares, and 2) to develop a mathematical model to estimate the weight of pregnant mares using body measurements. Thirty-four criollo-type mares were evaluated every two weeks during the middle and late pregnancy. The mares were weighed on a livestock scale, and we estimated body weight using tape weights and an associated body-weight estimation formula. Also, heart-girth circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Especially for young or pregnant horses, regular measurement and recording of BW is extremely important. Weight scales are the most reliable method of measurement, but a scale is often not available at horse farms [ 3 , 16 ]. According to the results of an online survey of horse owners, although more than half (60%) regularly monitored their horses’ weights, only 5% actually used weight scales [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for young or pregnant horses, regular measurement and recording of BW is extremely important. Weight scales are the most reliable method of measurement, but a scale is often not available at horse farms [ 3 , 16 ]. According to the results of an online survey of horse owners, although more than half (60%) regularly monitored their horses’ weights, only 5% actually used weight scales [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, body weight was not considered, which might also be considered a limitation of the investigation. Unfortunately, there was no availability of any scale on the farms where the experiment was performed, and indirect methods for body weight evaluation have not been applied since they are considered unreliable in pregnant mares 48 . Another important limitation was the absence of a control group of nonpregnant mares; the study was conducted on Italian Standardbred horse farms, in which most of the animals were pregnant, and there were not enough nonpregnant mares to enroll in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there was no availability of any scale on the farms where the experiment was performed, and indirect methods for body weight evaluation have not been applied since they are considered unreliable in pregnant mares. 48 Another important limitation was the absence of a control group of nonpregnant mares; the study was conducted on Italian Standardbred horse farms, in which most of the animals were pregnant, and there were not enough nonpregnant mares to enroll in the control group. Nonetheless, the placenta reaches full maturity only around day 150 of gestation, and cardiovascular alterations are not described in the first trimester of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in 2017 using the same brand of weigh tape found that it overestimated female horses by an average of 7.4 kg and underestimated the weights of male horses by an average of 7.5 kg [ 27 ]. However, 40% of the mares studied were pregnant at the time of measuring, and stage of pregnancy can also affect weigh tape readings [ 28 ]. Furthermore, of the non-pregnant subjects (male and female) in the 2017 study, 68% were under the age of five years (minimum of six months), so age-related conformational changes may not have been considered [ 25 ].…”
Section: Discussionmentioning
confidence: 99%